Analysis Of The Effect Of The Use Of Coral Reefs As A Substitute For Fine Aggregates On The Compressive Strength Of Concrete: ANALISIS PENGARUH PENGGUNAAN TERUMBU KARANG SEBAGAI SUBTITUSI AGREGAT HALUS TERHADAP KUAT TEKAN BETON - Ramadhan, Muhammad Fathur; Minaka, Utari Sriwijaya; Febriyandi (Universitas Negeri Surabaya, 2025)
Eco-friendly materials are in the spotlight of the world because they have a very influential impact on the development and advancement of technology today. Construction made of eco-friendly materials doesn’t damage nature, is lighter and use recycled materials. Coral reefs are a type of waste that can used to increase the compressive strength of concrete. This study analyzes the effect of using coral reef waste fragments as fine aggregate substitution of 70%, 75%, and 80%. The comparison was made against normal concrete without coral reef waste fragments. Compressive strength results were obtained in normal concrete of 25.93 MPa at the age of 28 days, while in concrete variations of coral reef waste fragments as fine aggregate substitution at the age of 28 days with variation of 70% of 28.18 MPa, variation of 75% of 26.48 MPa, and variation of 80% of 26.65 MPa. These results show that the use of coral reef waste fragments as fine aggregate substitution of 70% is the optimal result, and the use of coral reef waste fragments more than that can reduce the compressive strength of concrete, due to the excessive chemical compounds contained in coral reef waste, it can reduce the resistance to concrete.